Plyometric Training Favors Optimizing Muscle–Tendon Behavior during Depth Jumping - Hirayama, Kuniaki; Iwanuma, Soichiro; Ikeda, Naoki; Yoshikawa, Ayumi; Ema, Ryoichi; Kawakami, Yasuo (Frontiers in Physiology, 2017)
The purpose of the present study was to elucidate how plyometric training improves stretch–shortening cycle (SSC) exercise performance in terms of muscle strength, tendon stiffness, and muscle–tendon behavior during SSC exercise. Eleven men were assigned to a training group and ten to a control group. Subjects in the training group performed depth jumps (DJ) using only the ankle joint for 12 weeks. Before and after the period, we observed reaction forces at foot, muscle–tendon behavior of the gastrocnemius, and electromyographic activities of the triceps surae and tibialis anterior during DJ. Maximal static plantar flexion strength and Achilles tendon stiffness were also determined. In the training group, maximal strength remained unchanged while tendon stiffness increased. The force impulse of DJ increased, with a shorter contact time and larger reaction force over the latter half of braking and initial half of propulsion phases. In the latter half of braking phase, the average electromyographic activity (mEMG) increased in the triceps surae and decreased in tibialis anterior, while fascicle behavior of the gastrocnemius remained unchanged. In the initial half of propulsion, mEMG of triceps surae and shortening velocity of gastrocnemius fascicle decreased, while shortening velocity of the tendon increased. These results suggest that the following mechanisms play an important role in improving SSC exercise performance through plyometric training: 1) optimization of muscle–tendon behavior of the agonists, associated with alteration in the neuromuscular activity during SSC exercise and increase in tendon stiffness and 2) decrease in the neuromuscular activity of antagonists during a counter movement.